â€PROFIL USAHA INDUSTRI PENGOLAHAN BAWANG GORENG â€œGARUDA JAYAâ€ CV. DUTA AGRO LESTARI DI KELURAHAN BIROBULI KECAMATAN PALU SELATAN KOTA PALUâ€ - Andre A. Pandean; Lyndon R.J. Pangemanan; Tommy F. Lolowang; Ellen G. Tangkere (COCOS, 2015)
ABSTRACTPurpose of this study is to describe the profile of the business of â€œ Bawang Goreng Garuda Jaya" CV. Duta Agro Lestari based on the aspect of management, availability of raw materials, production processes, marketing, and finance.Based on the results obtained, it can be concluded that the CV. Duta Agro Lestari as a fried onion processing industry are included in the category of the industry. The company has 28 workers which divided into 7 permanent workers and 21 casual workers. The main raw materials used by the CV. Duta Agro Lestari is Sumenep red onion obtained from farmers, and supervised directly by the company. The production processing done daily during 3 days for each period of activity. All Fried onions product is packaged in a variety of models and sizes of packaging. Product marketing reach of the CV. Duta Agro Lestari is quite extensive, not only in the city of Palu, but also on the island of Sulawesi and Java,and singapore, Malaysia, Korea, and Japan. The faculty has two models of marketing channels.For one month, CV. Duta Agro Lestari receive a profit of Rp. 9,520,201.67 and the Break Even Point (BEP) of the business achieved with production of 1,274 kg.